Pengaruh Restrukturisasi Keuangan Terhadap Kinerja Perusahaan Grup Dan Non-Grup : Studi Kasus Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - As'ari, Hasim; Airawaty, Diana; Zaman, Badrus (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
Abstract This study aims to examine the differences in the effect of financial restructuring on the performance of group companies with non-groups in Indonesia. This analysis uses independent variables, debt restructuring, right issue and type of company. The dependent variable is ROA. The sample of this study is the issuer companies that conduct financial restructuring that are listed on the IDX from 2010 to 2016. 66 companies were analyzed using purposive sampling method. The statistical method uses Multiple Linear Regression Analysis, by testing the statistical test hypothesis t and Test F. The results of this study that there are significant and positive differences in debt restructuring, and Right Issue against performance group companies with non-group, which means that group companies are stronger in financial restructuring than non-group companies